Design of switching DC-DC converter - Edwin Darmawan Marelie (2010)
In order to design theswitching DC-DC Converter, different topologies has been researched in the current industry. A simple switching DC-DC buck converter with a stable feedback circuit and ability to suppress the ripple output voltage as small as possible had been successfully designed to meet the technical specification required for the project. It was designed using Cadence and simulated based on CSM 0.18um CMOS technology. The buck converter, operating at a fixed frequency of 100 kHz, was able to step down from the input supply voltage of 1.4 V to 1.8 V to a fixed output voltage of 1.2 V. Recommendations for future work include looking into the voltage loop compensation for a new compensation scheme and the inclusion of additional functions such as the protection circuitry, soft start etc.